Tanggung Jawab Notaris terhadap Akta Perjanjian Jual Beli Rumah yang Dikeluarkan Berdasarkan Keterangan Palsu oleh Para Pihak : (Studi Putusan Pengadilan Nomor 433/Pdt.G/2021/PN.Mdn) - Devira Ramadhani; Hasim Purba; Sutiarnoto (CV Rewang Rencang, 2025)
A notary’s official duties and authority are not solely for personal interest, but also serve the public interest. A notary is obligated to ensure the truthfulness of the deeds they draw up. Therefore, a notary is expected to act with honestly, fairness and transparency in preparing authentic deeds to safeguard all parties directly involved. This study employs a normative legal research method, using primary, secondary, and teriary legal materials, analyzed qualitatively. In the Courd Decision Number 433/Pdt.G/2021/ PN Mdn, the panel of judges considered that if a notary is proven to have knowingly or negligently include false information in a deed, this contitues both a violation of the notarical code of ethics and unlawful act. As a concequence, the notarial deed in question, being based on false statements, in declrared null and void by law.